Beyond accuracy: leveraging ASSURED criteria for field evaluation of point-of-care tests for food animal diseases - Ochwo, Sylvester; Perez, Andres M.; Pérez Aguirreburualde, María Sol (Frontiers in Veterinary Science, 2023)
The growing availability of point-of-care tests (POCTs) for food-animal diseases offers opportunities for timely diagnosis, facilitating the efficient implementation of control measures. However, field assessment of new POCTs are yet to be standardized. This paper discusses the opportunity of expanding the current approach for the evaluation and validation of POCTs in food animal disease diagnosis, highlighting the limitations of traditional practice that primarily relies on estimating diagnostic accuracy (sensitivity and specificity). Here, the use of a protocol referred to as FIT-REASSURED, a modified framework combining the ASSURED and REASSURED criteria, is proposed to comprehensively assess POCTs. FIT-REASSURED encompasses key criteria such as fitness for purpose, real-time connectivity, ease of specimen collection, affordability, sensitivity, specificity, user-friendliness, rapidity and robustness, equipment-free operation, and deliverability. By incorporating these attributes, FIT-REASSURED provides a customizable approach to assess the accuracy, affordability, and utility of POCTs. Through collaborative efforts among stakeholders, the implementation of a standardized scorecard based on these FIT-REASSURED criteria can improve the reliability and practicality of POCTs in food-animal health.